NON-UNIFORM APPROACH TOWARDS DATIVIZABLE VERBS - Sówka, Katarzyna (Acta Neophilologica, 2007)
Dative Altemation has given rise to a lot of controversy in the linguistic studies, especially in the reference to the inherent meaning of give verbs and its relation to the arguments projection. The aim of this paper is to provide support to Rappaport Hovav and Levin (2005) thesis that challenges a recently prevailing polysemy approach, which characterizes dativizable verbs of giving as having two inherent meanings. To provide data and support to Levin and Rappaport Hovav (2005) proposal concerning monosemy of dativizable give verbs, first, I point out drawbacks in the polysemy approach towards verbs o f giving, future having, and verbs o f communicated message in English. This analysis takes issue with the assumptions of the polysemy approach and supports the monosemy approach to give verbs in English. In order to give more support to this observation, later, I carefully scrutinize the equivalents of English verbs o f giving, future having and verbs o f communicated message in German and Polish. Both these languages show the equivalent of the Dative Alternation. The data provided from other languages demonstrates that verbs o f giving and their subtypes inherently involve only possession in their root meanings and exclude caused movement.